Přínos venkovského cestovního ruchu ke stabilizaci evropských zemědělských regionů - Lacina, Karel (Univerzita Pardubice, 2007)
The country tourism industry became the significant phenomenum not only in the Czech Republic but also in other European countries. It is contributing – and it has the potential to contribute more then in the previous years – to the regions development as well as to the implementation of regional strategic plans. The article is, therefore, oriented towards the characteristics of its role in the topical regional economic and social problems solution.
Keywords: country tourism industry; sustainable tourism activities; agro – tourism; eco – tourism; tourism industry environmental aspects; micro - regions